Protection mechanism of β-carotene on the chlorophyll photostability through aggregation: a quantum chemical perspective - Fangwei Li; Suxia Shen; Zhaotian Yang; Jinghao Zhang; Ajibola Nihmot Ibrahim; Yan Zhang (Food Innovation and Advances)
Chlorophyll (Chl), the most widely distributed natural pigment in nature, is limited in use due to its poor stability. This study refers to the aggregation structure of Chl and carotene (Car) in natural photosynthetic systems, hoping to improve the photostability of Chl by constructing Chl/Car aggregates. The stability protection effect of Car on Chl was explored by designing different ratios of Chl and Car aggregation systems. The configuration of Chl/Car aggregates was optimized through ab initio molecular dynamics, and the aggregation mechanism of the aggregates and the photoprotection mechanism of Chl by Car were elucidated through quantum chemical calculations and wave function analysis. Chl/Car had a 27.22% higher Chl retention rate than free Chl after 7 d of illumination, with a Chl to Car ratio of 1.66:1. A configuration of the Chl/Car aggregates which Car's conjugated olefin chain interacts extensively with the porphyrin ring and bent phytyl chain of Chl made them more stable. The photoprotective mechanism of Car on Chl in the Chl/Car aggregates is elucidated. Car's conjugated polyene chain provides HOMO orbitals to the Chl/Car aggregates. It demonstrated that Car supplies electrons in the low-lying excited states S2 and S4, indicating it is more susceptible to damage, protecting Chl. This research will promote the development of natural color formulas and ensure the health of consumers.